KOMUNIKASI INTERPERSONAL PETUGAS DALAM MEMBERIKAN PELAYANAN TERHADAP TAHANAN HINDU BALI BERBEDA KASTA DI RUTAN KELAS IIB KLUNGKUNG - Anak Agung Gede Maha Mulia Putra; Wido Cepaka Warih (Jurnal Komunikasi Hukum, 2024)
The State Detention Center (Rutan) plays a vital role in Indonesia's correctional system, particularly in providing services to inmates, as mandated by Law No. 22 of 2022, Article 60, Paragraph 1. These services include fulfilling the basic needs of inmates such as nutritious food, clean water, healthcare, and hygiene. At Rutan Class IIB Klungkung, under the Regional Office of the Ministry of Law and Human Rights in Bali, interpersonal communication by staff is crucial in delivering services to inmates, including Hindu Balinese inmates of different castes. This research aims to analyze the forms, roles, and impacts of staff's interpersonal communication in providing equal and fair services to Hindu Balinese inmates from various castes at Rutan Class IIB Klungkung. Using a qualitative approach, this study explores how caste differences affect interactions between staff and inmates and examines used to overcome communication barriers in providing services to Hindu Balinese inmates of different castes. The findings of this research are expected to provide insights into the importance of effective and inclusive communication within the context of correctional services, especially in dealing with socio-cultural dynamics such as caste differences.